(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the prevalence of Human Immunodeficiency Virus (HIV) infection and risk factors associated with transmission in pregnant women of a public maternity hospital in Piauí. The cutoff point was October 2015 and June 2016, where data were collected from 412 pregnant women up to 26 years of age, related to sociodemographic characteristics, factors associated with infection, and obstetric and gynecological factors. Correlations were verified by Chi-square test (χ2), establishing a significance level below 5% (p <0.05). The prevalence of HIV infection among pregnant women was 2.2%. There was a significant association between maternal HIV infection and illicit drug use (p = 0.027), intravenous illicit drug use (p = 0.02) and abortion (p = 0.005). In contrast, there was no significance in the association with other factors, such as age, occupation, number of partners and sexual orientation of the pregnant woman. Thus, it was observed that the prevalence of pregnant women with HIV in the maternity hospital in question is considerably high. In addition, most of these pregnant women were in a state of social vulnerability.